Effects of additives on sonolytic degradation of azo dye molecules found in industrial wastewater - Monira, Shirajum; Ashifuzzaman, Md.; Islam, Md. Monjurul; Hossain, Md. Jahangir; Okitsu, Kenji; Rahman, Md. Hafizur; Islam, Md. Shaharul; Uddin, Md. Helal (Penerbit Universiti Kebangsaan Malaysia, 2022)
The growing number of industries is a threat to our environment, as they expose the polluted water directly into the natural water sources. Various processes have been expanded to evacuate these hazardous organic pollutants from water. Among them, advance oxidation process (AOP) is very popular, as the method is cost efficient and highly effective in the similar field. In this process ultrasound is exercised for the deterioration of these pollutants and occasionally some additives are also added to enhance the degradation. In this article, the author has reported the degradation of two azo dyes, named methyl orange (MO) and congo red (CR), in presence of some additives like, inorganic salts, charcoal, H2O2, CCl4, tert-butyl alcohol (TBA), glucose and sucrose. The total experiment was conducted at room temperature and the power of the sonication machine was fixed to 40 kHz-120W. For both of the dyes, it was found that charcoal was most effective additive, which highly enhanced the degradation rate, which was mainly due to its high adsorption capability. TBA found to be the least enhancer for MO, on the contrary, pure CR showed the lowest degradation rate. The effectiveness of additives for MO can be shown as 0.01g charcoal > 20 ml glucose > 20 ml NaCl > 100 μL CCl4 > 10 ml Na2SO4 > 400 μL H2O2 > 10 ml sucrose > pure MO > TBA, while for CR is 0.01g charcoal > combined additives > TBA > 100 μL CCl4 > pure CR, after sonication for 15 minutes in a sonicator.